2016
DOI: 10.1590/s1679-45082016ao3747
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Spoken Knowledge in Low Literacy Patients with Diabetes in Brazilian elderly

Abstract: Objective To translate, adapt and evaluate the properties of a Brazilian Portuguese version of the Spoken Knowledge in Low Literacy Patients with Diabetes, which is a questionnaire that evaluate diabetes knowledge.Methods A cross-sectional study with type 2 diabetes patients aged ≥60 years, seen at a public healthcare organization in the city of Sao Paulo (SP). After the development of the Portuguese version, we evaluated the psychometrics properties and the association with sociodemographic and clinical varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
0
15
0
8
Order By: Relevance
“…In Brazil, there is not a research of national amplitude showing the HL level of the population (4) ; however, there are studies that validated measurement instruments of this construct for the Portuguese language (12) and classified levels of health literacy of people with specific health problems (5,11,14) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, there is not a research of national amplitude showing the HL level of the population (4) ; however, there are studies that validated measurement instruments of this construct for the Portuguese language (12) and classified levels of health literacy of people with specific health problems (5,11,14) .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the studies conducted in Brazil have assessed the HL of individuals in specific populations, such as adults and seniors (1,(11)(12) , people with distinct health aggravations, such as diabetes (5,13) , cardiovascular diseases (14) and chronic kidney disease (15) , or in individuals in continuous use of medicines (16) , but only few studies assessed the HL of adults with hypertension (15) , in particular those who are treated in the Primary Health Care (PHC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Moreover, poor health literacy is found to be associated with worse glycemic control and a higher risk of complications. 14 Among patients with hypertension, significant differences were present depending on the education status of subjects. Similarly, unemployed patients also had lesser understanding of the information provided by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The care programs of a multidisciplinary collaborative care model for hospitalized diabetic elders were established by centralized consultation, reducing the repeated nursing consultation time of older diabetic patients with multiple diseases and thus effectively shortening the hospital stay [24,25]. In the multidisciplinary team teamwork model, all nursing staffs have a new and improved understanding in the care theory of older patients with diabetes through business study, pathological discussion, bedside rounds, and head nurse on-site management [7,[26][27][28]. Through the multipronged cooperation, the overall level of disease management around patients has been raised.…”
Section: Discussionmentioning
confidence: 99%